Maternal Hypovitaminosis D as a Cause of neonatal seizure - Yoriko Nishizawa; Sonam Sonam; Carolyn Mize; Tamara Vesel (Bhutan Health Journal, 2017)
Maternal hypovitaminosis D has many implications for both mother and newborn. The prevalence of vitamin D deficiency in Bhutan is not yet known. The case presented below represents a severe symptomatic presentation of vitamin D deficiency in a neonate due to maternal vitamin D deficiency. It highlights the need for raised suspicion of vitamin D deficiency as a cause of late-onset neonatal seizures, epidemiologic studies, and potential vitamin supplementation for pregnant women, as well as the need for vitamin D-only liquid supplements in pharmacies in Bhutan.